1998
DOI: 10.1002/(sici)1096-9861(19980420)393:4<403::aid-cne1>3.3.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Localization of mRNA encoding the P2X2 receptor subunit of the adenosine 5′‐triphosphate‐gated ion channel in the adult and developing rat inner ear by in situ hybridization

Abstract: Localization of expression of the adenosine 5'-triphosphate (ATP)-gated ion channel P2X2 receptor subunit (P2X2R) in the rat inner ear at different stages of development was achieved by using in situ mRNA hybridization. In the adult, P2X2R mRNA was strongly expressed in many of the cells bordering the cochlear endolymphatic compartment. This included the interdental cells of the spiral limbus, all cells of the inner sulcus and organ of Corti, and cells of the spiral prominence. In the vestibular labyrinth, str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 0 publications
3
17
1
Order By: Relevance
“… 51–53 A number of experiments suggest that this decline originates from the considerable P2X receptor shunt conductance of the various tissues that, in addition to the hair cells, line scala media, with the major exception of the marginal cells of the stria vascularis. 4,54 Analysis of the cochlear partition resistance during injection of ATP into endolymph shows a linear correlation between ATP‐induced decline in EP and decrease in resistance (increased conductance). 33 In cochleas treated with aminoglycoside antibiotics to selectively destroy the hair cells, the effect is still present.…”
Section: P2x Receptors As Shunt Conductorsmentioning
confidence: 99%
See 2 more Smart Citations
“… 51–53 A number of experiments suggest that this decline originates from the considerable P2X receptor shunt conductance of the various tissues that, in addition to the hair cells, line scala media, with the major exception of the marginal cells of the stria vascularis. 4,54 Analysis of the cochlear partition resistance during injection of ATP into endolymph shows a linear correlation between ATP‐induced decline in EP and decrease in resistance (increased conductance). 33 In cochleas treated with aminoglycoside antibiotics to selectively destroy the hair cells, the effect is still present.…”
Section: P2x Receptors As Shunt Conductorsmentioning
confidence: 99%
“…As noted, the stria vascularis appears as the exception to the general expression of P2X 2 receptors by cells lining scala media. 4,54 Interestingly, the marginal cells within the stria are responsible for the K + influx into scala media and provide the electrical window for the generation of EP by the ion transporters associated with the confluence with the underlying intermediate cell layer. 49 This window into the endolymph occurs via K + channels assembled from KvLQT1 subunits and IsK regulatory subunits, which, in rat and gerbil (and humans), is regulated by a PKC phosphorylation site present on the IsK subunit.…”
Section: Purinergic Modulation Of Endolymphatic K+ Transport Influencmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have confirmed that the P2X 2 subunit of the ATP‐gated ion channel is abundantly expressed in cochlear tissues. P2X 2 receptor subunits have been identified in hair cells and supporting cells by using the reverse transcription‐polymerase chain reaction (RT‐PCR) technique (Glowatzki et al, 1995; Housley et al, 1995; Brändle et al, 1997, 1999; Housley and Ryan, 1997; Housley et al, 1999) and by in situ hybridization (Housley and Ryan, 1997; Housley et al, 1998b; Parker et al, 1998). P2X 2 subunits also have been detected in Reissner's membrane, which separates the endolymphatic from the perilymphatic compartment (King et al, 1998; Housley et al, 1999).…”
mentioning
confidence: 99%
“…Given the putative roles of extracellular ATP and P2 receptors in hearing, it is of clear interest to know the spatiotemporal expression of P2X 2 receptors in the developing labyrinth. Expression of mRNA for P2X 2 was recently localized in the developing rat cochlea by using in situ hybridization (Housley et al, 1998b). Expression was detected in epithelial tissues of the otocyst as early as embryonic day 12 (E12).…”
mentioning
confidence: 99%